Single-Stage Bipedicle Local Tissue Transfer and Skin Graft for Achilles Tendon Surgery Wound Complications. Issue 1 (February 2017) - Dekker, Travis J.; Avashia, Yash; Mithani, Suhail K.; Matson, Andrew P.; Lampley, Alexander J.; Adams, Samuel B.
Introduction . Achilles tendon and posterior heel wound complications are difficult to treat. These typically require soft tissue coverage via microvascular free tissue transfer at a tertiary referral center. Here, we describe coverage of a series of posterior heel and Achilles wounds via simple, local tissue transfer, called a bipedicle fasciocutaneous flap. This flap can be performed by an orthopaedic foot and ankle surgeon, without resources of tertiary/specialized care or microvascular support. Methods . Three patients with separate pathologies were treated with a single-stage bipedicle fasciocutaneous local tissue transfer. Case 1 was a patient with insertional wound breakdown after Achilles debridement and repair to the calcaneus. Case 2 was a heel venous stasis ulcer with calcaneal exposure in a diabetic patient with vasculopathy. Case 3 was a patient with wound breakdown following midsubstance Achilles tendon repair. All three cases were treated with a single-stage bipedicle local tissue transfer for posterior ankle and heel wound complications. Results . All 3 patients demonstrated complete healing of the posterior defect, lateral ankle skin graft recipient site, and the skin graft donor site after surgery. Case 3 had a subsequent recurrent ulceration after initial healing. This was superficial and healed with local wound care. All patients regained full preoperative range of motion and were able to ambulate independently without modified footwear. Conclusions . The bipedicled fasciocutaneous flap described here offers a predictable single stage procedure that can be accomplished by an orthopaedic foot and ankle surgeon without resources of a tertiary care center for posterior foot and ankle defects. This flap can be performed with short operative times and can be customized to facilitate defect coverage. The flap is durable to withstand local tissue stresses required for early ambulation. Despite its reliability, patients require careful follow-up to manage underlying comorbid conditions that may complicate wound healing. Levels of Evidence: Level IV: Case series